Upaya Amerika Serikat Dalam Menanggulangi Pelanggaran Hak Kekayaan Intelektual Pada Masa Kepemimpinan Donald Trump - Naufal Muhammad Firdaus (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2019)
The United States as a developed country in industry and economy certainly has innovative and sustainable intellectual property. However, if Intellectual Property Rights are misused by other people or other countries with the appearance of many imitations based on the same ideas or goods as owned by the United States, it will cause harm to the United States itself. For this reason, the United States during the administration of Donald J. Trump viewed the protection of Intellectual Property Rights as a very important matter. The efforts of the United States itself in protecting it are also considered to be very serious, where the United States through its main institution called the Office of the US Intellectual Property Enforcement Coordinator (IPEC) as well as several other institutions that help, are working hard each year to promote and protect the Intellectual Property Rights that are owned by the United States both bilaterally, multilaterally and regionally. In this case, the United States of America is also firm in upholding the law on Intellectual Property Rights and does not hesitate if there are countries that violate their Intellectual Property Rights by providing various economic sanctions.